Omentum a powerful biological source in regenerative surgery - Di Nicola, Valerio (Regenerative therapy, 2019)
The Omentum is a large flat adipose tissue layer nestling on the surface of the intra-peritoneal organs. Besides fat storage, omentum has key biological functions in immune-regulation and tissue regeneration. Omentum biological properties include neovascularization, haemostasis, tissue healing and regeneration and as an in vivo incubator for cells and tissue cultivation. Some of these properties have long been noted in surgical practice and used empirically in several procedures. In this review article, the author tries to highlight the omentum biological properties and their application in regenerative surgery procedures. Further, he has started a process of standardisation of basic biological principles to pave the way for future surgical practice.